PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, KEPUASAN KERJA, DAN BUDAYA ORGANISASI TERHADAP PERILAKU EKSTRA PERAN PEGAWAI NEGERI SIPIL PADA BALAI PEMANTAPAN KAWASAN HUTAN WILAYAH XVI PALU - Supriyono, Supriyono (Katalogis, 2015)
The purpose of this research is to explore and analyze the influence of transformational leadership, job satisfaction, and organizational culture on organizational citizenship behavior of officials in the office of forest consolidation region XVI, Palu. The sample of this study consists of 35 officials in the office of forest consolidation region XVI, Palu, which is selected through census sample method. The result of t-test and regression analysis indicate that variable of transformational leadership, job satisfaction, and organizational culture on organizational citizenship behavior of officials in the office of forest consolidation region XVI, Palu. Determinant test shows Adjusted R-Square value of 0.640, which means that organizational citizhenship behavior is influenced by the independent variables that are transformational leadership, job satisfaction, and organizational culture. While the remaining value is indicated by other variable that is not included in the study.